2015
DOI: 10.1038/ijos.2015.47
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin and vitamin D3 have high therapeutic potential for improving diabetic mandibular growth

Abstract: The goal of this study was to assess the effect of the intermittent combination of an antiresorptive agent (calcitonin) and an anabolic agent (vitamin D3) on treating the detrimental effects of Type 1 diabetes mellitus (DM) on mandibular bone formation and growth. Forty 3-week-old male Wistar rats were divided into four groups: the control group (normal rats), the control C+D group (normal rats injected with calcitonin and vitamin D3), the diabetic C+D group (diabetic rats injected with calcitonin and vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…Periodontitis results when AGEs react with receptors of advanced glycosylation end products (RAGEs), in the periodontal tissues. Furthermore, animal studies suggest that DM not only induces higher alveolar bone resorption but also alters orthodontic tooth movement [ 14 , 15 ]. In addition, studies suggest that DM inhibits bone remodeling around the teeth undergoing orthodontic tooth movement [ 16 , 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…Periodontitis results when AGEs react with receptors of advanced glycosylation end products (RAGEs), in the periodontal tissues. Furthermore, animal studies suggest that DM not only induces higher alveolar bone resorption but also alters orthodontic tooth movement [ 14 , 15 ]. In addition, studies suggest that DM inhibits bone remodeling around the teeth undergoing orthodontic tooth movement [ 16 , 17 ].…”
Section: Reviewmentioning
confidence: 99%
“…The availability of more effective osteoporosis drugs, such as bisphosphonates, has led to CT therapy primarily being used for the short‐term mediation of acute pain from osteoporosis, although combination treatments involving CT have shown efficacy in mediating both hypercalcemia and bone quality under circumstances in which other treatments were ineffective . In particular, CT has seen significant use as a therapeutic for the treatment of postmenopausal osteoporosis ,,,.…”
Section: Current Calcitonin Therapymentioning
confidence: 99%
“…Relatively of "the stomatognathic system", Mona et al suggested that supplementation of vitamin D combined with an antiresorptive agent (calcitonin) may enhance mandibular growth and potentially produce a beneficial effect on orthodontic treatment for stunted mandibular bone growth problems [70].…”
Section: Discussionmentioning
confidence: 99%